Exercise Training Prevents Decrease in Luminal Capillary Diameter of Skeletal Muscles in Rats with Type 2 Diabetes - Takeshi Morifuji; Shinichiro Murakami; Naoto Fujita; Hiroyo Kondo; Hidemi Fujino (The Scientific World Journal)
The purpose of this study was to examine whether exercise training can prevent microangiopathy of skeletal muscles in rats with type 2 diabetes and if succinate dehydrogenase (SDH) activity, an indicator of mitochondrial oxidative enzyme activity, is involved in the prevention of microangiopathy. Six-week-old male Goto-Kakizaki (GK) rats and age-matched male Wistar rats (control group (Con)) were used. GK rats were randomly assigned to nonexercise (DB) and exercise (DBEx) groups. The DBEx group was trained on a treadmill 5 times a week for 3 weeks. No significant differences in the capillary-to-fibre ratio or the capillary density were observed between the 3 groups. The luminal capillary diameter of the DB group was significantly lower than that of the Con group, whereas the capillary diameter of the DBEx group was significantly higher than that of the DB group. In addition, SDH activity was significantly higher in the DBEx group than in the Con and DB groups. Microangiopathy of skeletal muscles in type 2 diabetes was correlated with a decrease in the luminal capillary diameter, which was prevented by exercise training. Thus, the mitochondrial oxidative capacity appears to be involved in the overall mechanism by which exercise prevents microangiopathy.